Can the Chinese Nation Be One? Gu Jiegang, Chinese Muslims, and the Reworking of Culturalism. (November 2019) - Jenco, Leigh K.
This article examines how the classicist and folklorist Gu Jiegang, in conversation with his Hui (Chinese Muslim) colleagues at the Yugong study society and journal (published 1934–1937), theorized the "Chinese nation" ( Zhonghua minzu ) as an internally plural and open-ended political project, to resist homogenizing claims by both Japanese imperialists and the ruling Chinese Nationalist party under Chiang Kai-shek in the 1930s. Echoing the struggles of his Hui colleagues to articulate their place in the nation as both Muslim and Chinese, Gu reworked traditional "culturalist" assumptions about the non-racial character of identity formation to pose minority experience as constitutive of a constantly expanding and transforming political community. When Gu asserted in his notorious 1939 essay that the " Zhonghua minzu Is One, " he posed a unity built not on cultural assimilation or ethnic identity, but on a shared political commitment to an expansive and culturally hybrid concept of the "Chinese nation."